2009
DOI: 10.1089/ten.tec.2007.0334
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin Secretion as an Early Marker ofIn VitroOsteogenic Differentiation of Rat Mesenchymal Stem Cells

Abstract: Osteocalcin (OC) is a bone-specific protein synthesized by osteoblasts that represents a good marker for osteogenic maturation. We examined whether in vitro osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (MSCs) could be simply assessed at earlier stages by monitoring OC secretion into the conditioned medium, rather than measuring OC deposition on the extracellular matrix (ECM), using a sandwich enzyme immunoassay system involving a specific anti-rat OC monoclonal antibody. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(158 citation statements)
references
References 31 publications
7
148
2
1
Order By: Relevance
“…A cohort of gene transcripts and key osteogenic-related proteins (RUNX-2, OCN, NOG, SP-1) were identified that correlate to the early histological response and development of ectopic bone. RUNX-2 is the early master regulator of osteogenic/osteoblast differentiation [16], and OCN is a prime marker of bone development produced by osteoblasts [18]. SP-1 is a neuroinflammatory peptide that has been reported to promote the mobilization, proliferation, and osteogenic differentiation of mesenchymal stem cells at sensory nerve structures [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort of gene transcripts and key osteogenic-related proteins (RUNX-2, OCN, NOG, SP-1) were identified that correlate to the early histological response and development of ectopic bone. RUNX-2 is the early master regulator of osteogenic/osteoblast differentiation [16], and OCN is a prime marker of bone development produced by osteoblasts [18]. SP-1 is a neuroinflammatory peptide that has been reported to promote the mobilization, proliferation, and osteogenic differentiation of mesenchymal stem cells at sensory nerve structures [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…10 mg of each reagent was dissolved in 20 ml of AMP buffer (1.0 mM MgCl 2 , 10 mM p-nitrophenyl phosphate in 0.056 M 2-amino-2-methyl-propanol). Cells were incubated with 2 ml of the substrate solution at room temperature for ~2 minutes and rinsed with dH 2 O. Alizarin Red S (0.5%) was also used to evaluate calcium deposition, following which cells were rinsed with dH 2 O [12,18]. Each experiment contained 3 replicates and was performed in duplicate.…”
Section: Alp and Alizarin Red S Stainingmentioning
confidence: 99%
“…Cells cultured in 12-well culture plates were used to measure ALP activity, as previously reported [12]. Briefly, P1, P2 and P3 cells, seeded in 12-well plates at a density of 1 × 10 4 cells/cm 2 and cultured for 14 days with or without osteogenic-induced media containing Dex, ascorbic acid phosphate and β-GP, were scraped into 1 ml of 0.05 M sodium phosphate buffer, 2 mM EDTA and 2 M NaCl, following which they were homogenized and sonicated.…”
Section: Alp Activity Calcium and Dna Concentration In Vitromentioning
confidence: 99%
See 2 more Smart Citations